An Advanced Real Time Lead RF-MEMS Based Switch Design for AI Applications - S, Girish Gandhi; I, Govardhani; M, Venkata Narayana (International Journal of Integrated Engineering, 2022)
The artificial intelligence-based MEMS switch designs have been led technology in present micro-electronic applications. The 4G and 5G communication hardware networks have working been through RF-MEMS switches. The earlier MEMS deigns are outdated in terms of functionality and compatibility, so that a realistic RF-MEMS based advanced configurations are compulsory for future electronic applications. In this research work 2 different shunt-capacitive type configurations have been implemented and those are verified on COMSOL Multi-physics toolbox as well as functionality been verified on HFSS software tool. The electromechanical properties of proposed shunt type RF-MEMS switch attained more perfection in functionality compared to past configurations. The implemented switching model has uniform meandering and derives pull-in-voltage of 18.5v along with 1.2xs switching time. The 2nd type shunt RF-MEMS model has been generated pull-in-voltage of 25.5v and isolation loss of 37.20. The performance metrics like Length 25.34 µm, Width 28.92 µm and Thickness 34.42 µm had been improved compared to previous models. The deigned shunt-capacitive type RF-MEMS models are most prominent in operation and offering advanced microelectronics applications.